Association of statins, aspirin, and venous thromboembolism in women with endometrial cancer - Matsuo, Koji (Gynecol Oncol, 2019)
OBJECTIVE: The anti-thrombogenic effects of statins and aspirin have been reported in various malignancies but have not been well examined in endometrial cancer. This study examined the association between statin and/or aspirin use and venous thromboembolism (VTE) risk in endometrial cancer. METHODS: This is a multi-center retrospective study examining 2527 women with endometrial cancer between 2000 and 2015. Statin and aspirin use at diagnosis was correlated to VTE risk during follow-up on multivariable analysis. RESULTS: There were 132 VTE events with a 5-year cumulative incidence rate of 6.1%. There were 392 (15.5%) statin users and 219 (8.7%) aspirin users, respectively. On multivariable analysis, statin use was associated with an approximately 60% decreased risk of VTE when compared to non-users (5-year cumulative rates 2.5% versus 6.7%, adjusted-hazard ratio [HR] 0.42, 95% confidence interval [CI] 0.19–0.92, P = 0.030) whereas aspirin did not demonstrate statistical significance (2.0% versus 6.5%, adjusted-HR 0.54, 95%CI 0.19–1.51, P = 0.24). There was a trend of joint effect between statin and aspirin although it did not demonstrate statistical significance: VTE risks for dual statin/aspirin user (adjusted-HR 0.27, 95%CI 0.04–2.07), statin alone (adjusted-HR 0.40, 95% CI 0.18–0.93), and aspirin alone (adjusted-HR 0.51, 95%CI 0.16–1.64) compared to non-use after adjusting for patient characteristics, tumor factors, treatment types, and survival events (P-interaction = 0.090). When stratified by statin type, simvastatin demonstrated the largest reduction of VTE risk (5-year cumulative rates 1.1% versus 6.7%, adjusted-HR 0.17, 95%CI 0.02–1.30, P = 0.088). Obesity, absence of diabetes mellitus, type II histology, and recurrent disease were the factors associated with decreased VTE risk with statin use (all, P-interaction<0.05). CONCLUSION: Our study suggests that statin use may be associated with decreased risk of VTE in women with endometrial cancer.